2016
DOI: 10.1007/s10926-016-9640-7
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Return-to-Work Coordinators Working in Large Organizations

Abstract: Purpose Although the role of return-to-work coordinators (RTW coordinators) is associated with reducing long-term disabilities, little has been written about their practices. The objective of this study was to clearly identify their tasks and activities and the stakeholders with whom they collaborate. Methods A cross-sectional survey was conducted using a web-based self-administered questionnaire. Participant inclusion criteria were as follows: (1) working for a large organization with 500 or more employees; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 11 publications
2
33
0
1
Order By: Relevance
“…A majority of those with a traumatic SCI in Sweden are in working age [59], and coordination of RTW derived from the SCI rehabilitation setting has the potential of organising the early RTW process for them. The use of coordinators is increasingly reported [35][36][37][38][39][40], and coordination of RTW within healthcare is legally required in Sweden [30]. Yet, persons with SCI in Sweden typically lack coordinator availability, and the evidence for coordination of RTW is still uncertain [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of those with a traumatic SCI in Sweden are in working age [59], and coordination of RTW derived from the SCI rehabilitation setting has the potential of organising the early RTW process for them. The use of coordinators is increasingly reported [35][36][37][38][39][40], and coordination of RTW within healthcare is legally required in Sweden [30]. Yet, persons with SCI in Sweden typically lack coordinator availability, and the evidence for coordination of RTW is still uncertain [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…These are: challenges to coordination [31]; divergent perspectives on work ability assessments [32,33]; fragmentation of the RTW process due to lack of routines [31,32]; and lack of knowledge about others' expertise and capacity for actions [31,34]. As a response to poor coordination of RTW, integration of services using a coordinator is being increasingly reported internationally [35][36][37][38][39] and is also described in Sweden [40]. The evidence for such services is still uncertain [41,42] and implementation strategies vary [41].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of RTW-coordinators revealed the activities of workplace assessment, planning transitions and facilitating stakeholder cooperation with focus on communication and problem solving [16, 22]. Still, a recently published Canadian paper concludes that the integration of services is far below recommendation [23]. Instead, the RTW-coordinators in large companies mostly focused on the employee-supervisor dyad, a horizontal integration, and did not coordinate towards health and welfare services or other stakeholders [23].…”
Section: Introductionmentioning
confidence: 99%
“…Still, a recently published Canadian paper concludes that the integration of services is far below recommendation [23]. Instead, the RTW-coordinators in large companies mostly focused on the employee-supervisor dyad, a horizontal integration, and did not coordinate towards health and welfare services or other stakeholders [23].…”
Section: Introductionmentioning
confidence: 99%
“…Les absences dues à un trouble mental peuvent aussi avoir un impact sur les collègues qui doivent parfois absorber le travail de l'employé absent. Au Québec comme ailleurs, nombreux sont les gestionnaires qui se questionnent sur la gestion de l'absence de l'employé et son éventuel retour dans l'équipe de travail 11 .…”
unclassified